Analysis of the Impact of China’s Green Finance Pilot Policies on Carbon Emission Reduction in Pilot Areas - Pan, Ziyuan (2024)
Realizing carbon reduction cannot solely rely on market regulation but also requires effective environmental policies enacted by the government, and green finance is one of the important policy tools. China's pilot policies on green finance explore the use of various green financial instruments, providing an excellent opportunity to study the role of green finance in carbon reduction. This study, based on provincial and municipal panel data from 1997 to 2021 in China, takes the issuance of pilot green finance policies as a quasi-natural experiment and employs a difference-in-differences model to evaluate the impact of pilot green finance policies on carbon reduction. The hypothesis proposed in this paper is that pilot green finance policies have a significant positive impact on carbon reduction. The empirical analysis indicates that although the results suggest a positive influence on carbon reduction, statistical significance is not attained, possibly due to local government variations in policy implementation. Additionally, the study underscores the importance of technological advancement and infrastructure in achieving tangible carbon reduction outcomes, highlighting potential limitations in industries or regions lacking appropriate clean technologies or infrastructure. These findings offer valuable insights for global efforts towards carbon neutrality.